1995
DOI: 10.1080/09603129509356852
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence ofPseudomonas aeruginosapyocin and antibiotic biotypes in four Tehran hospitals

Abstract: Over a 15-month period, 340 strains of Pseudomonas aeruginosa were isolated from clinical specimens, i.e. sputum, wound swabs, pus, burns, urine, stool, etc., and the environment, i.e. sink, floor, bed sheets, etc., in four Tehran hospitals. Identification of Pseudomonas aeruginosa was carried out by standard methods. Pyocin typing and subtyping were done using the spotting method of Govan, and using a set of 13 indicator strains. Results of the study showed that the dominant pyocin types were PT10, PT4 and PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
(15 reference statements)
0
1
0
Order By: Relevance
“…[67] reported Pseudomonas isolates that were resistant to only single antibiotics, all the tested isolates in this study showed multiple antibiotic resistances (MARs) ranging from five to 11 antibiotics distributed among three to seven classes. Consistent with the observation of this study, Paul et al .…”
Section: Discussionmentioning
confidence: 83%
“…[67] reported Pseudomonas isolates that were resistant to only single antibiotics, all the tested isolates in this study showed multiple antibiotic resistances (MARs) ranging from five to 11 antibiotics distributed among three to seven classes. Consistent with the observation of this study, Paul et al .…”
Section: Discussionmentioning
confidence: 83%